The effect of verbotonal rehabilitation on visual evoked potentials in dyslexic children - Vranić, Đurđica (Array, 2007)
Evoked visual potentials testing with cortical cartography shows as useful diagnostic method for visualisation of functional changes in visual pathway in dyslexic children. The aim of this study was to investigate the changes in visual evoked potentials and cartographical characteristics in dyslexic children after one year of verbotonal rehabilitation. Twenty dyslexic children aged 7-10 years were tested. Control group consisted of 20 healthy children, matched by age, gender and nonverbal status. Complete diagnostic evaluation were performed included ophtalmological, otoneurological, logopedic and psychological evaluation. Subjects and controls were examined by checkerboard pattern reversal visual evoked potentials (VEP) according to the 2004. European standards. Cortical cartography was simultaneously performed by Neuroscan 32-electrode system using Scan 4.3 software for data analysis. The results show significantly delayed latency of N 135 wave during monocular and binocular stimulation in dyslexic children. Twelve children show significant functional assymetry in monocular stimulation, ten of them show are decompensated in binocular analysis of visual information. After one year of rehabilitation the significat shortening of wave N 135 latency has been recorded in all subjects. The functional asimetry during monocular activation has been less expressed in five children, and eight subjects have achieved the compensation during binocular activation.